Research recruitment through the patient portal: perspectives of community focus groups in Seattle and Atlanta. Issue 1 (3rd February 2023) - Porter, Kathryn M; Kraft, Stephanie A; Speight, Candace D; Duenas, Devan M; Niyibizi, Nyiramugisha K; Mitchell, Andrea; O'Connor, M Rebecca; Gregor, Charles; Liljenquist, Kendra; Shah, Seema K; Wilfond, Benjamin S; Dickert, Neal W
Abstract: Objective: Research recruitment through patient portals (ie, patient-facing, web-based clinical interfaces) has the potential to be effective, efficient, and inclusive, but best practices remain undefined. We sought to better understand how patients view this recruitment approach. Materials and Methods: We conducted 6 focus groups in Atlanta, GA and Seattle, WA with members of patient advisory committees and the general public. Discussions addressed acceptability of patient portal recruitment and communication preferences. Focus groups were audio-recorded, transcribed, and analyzed using deductive and inductive codes. Iterative team discussions identified major themes. Results: Of 49 total participants, 20 were patient advisory committee members. Participants' mean age was 49 (range 18–74); 59% identified as non-Hispanic White and 31% as Black/African American. Participants were supportive of patient portal recruitment and confident that messages were private and legitimate. Participants identified transparency and patient control over whether and how to participate as essential features. Concerns included the frequency of research messages and the ability to distinguish between research and clinical messages. Participants also discussed how patient portal recruitment might affect diversity and inclusion. Discussion: Focus group participants generally found patient portal recruitment acceptable and perceived it as secure and trustworthy. Transparency, control, and attention to inclusiveness were identified as key considerations for developing best practices. Conclusion: For institutions implementing patient portal recruitment programs, continued engagement with patient populations can help facilitate translation of these findings into best practices and ensure that implemented strategies accomplish intended goals. Lay Summary: Healthcare systems are increasingly implementing, or considering implementation of, research recruitment functionality through the patient portal (ie, patient-facing, web-based clinical interfaces). To better understand the views of patients/potential research participants, we conducted 6 focus groups in Seattle, WA and Atlanta, GA, recruiting from the general public as well as members of a medical institution's patient advisory committee. Research recruitment through the patient portal was viewed favorably by our focus group participants. They reported feeling confident that patient portal messages were private and legitimate compared to other messaging approaches such as email. Transparency and patient control over whether and how to participate were viewed as important features of patient portal recruitment. Potential concerns included the frequency of research messages, the ability to distinguish between research and clinical messages, and how patient portal recruitment might impact diversity and inclusion. These findings support current efforts by healthcare systems to implement this recruitment method. Continued engagement with patient populations can help to facilitate translation of these findings into best practices and to ensure that implemented strategies accomplish their intended goals.